Influence of curing temperatures on the performances of fiber-reinforced concrete. (11th July 2022) - Lu, Jianguo; Liu, Junni; Yang, Huohai; Gao, Jiajia; Wan, Xusheng; Zhang, Jiacheng
Highlights: The influence of curing temperatures on the performances of FRCs were studied. The curing temperatures and curing ages have positive effects on the compressive strength of concrete. There is an optimum fiber content for the compressive strength of FRCs cured at low temperatures to resist loads. The added fibers into concrete improves the ductility of concrete due to the fiber bridging effect. The negative curing temperatures significantly inhibit the hydration reaction. Abstract: In cold regions or even permafrost areas, it shows growing interests in engineering infrastructures, and more engineering projects have been constructing, e.g. Sichuan-Tibet railway. Undoubtedly, the concrete needs to be cured at the temperature below the conventional curing temperature (about 20 °C). This paper investigated the effect of curing temperatures (i.e. −6 °C, −2 °C, 2 °C and 6 °C) on the performances (compressive strength, stress–strain relationship, microstructure, and hydration products) of steel fiber-reinforced concrete (SFRC), polypropylene fiber-reinforced concrete (PPFRC), and basalt fiber-reinforced concrete (BFRC). The results show that the curing temperature and curing age have positive effects on the compressive strength of concrete samples, and the compressive strength increases with the curing temperatures and curing ages. Besides, regardless of curing temperatures, the type and dosage of added fibers would greatly affect the compressive strength, and there is an optimum fiber content for the compressive strength of FRCs cured at the low temperature to resist loads, and the optimum fiber contents for the SFRC, PPFRC and BFRC are 2.0%, 2.0‰ and 0.5‰, respectively. Additionally, the axial stress–strain curves can be divided into four-section characteristics, i.e. linear ascending stage, plastic yield stage, descending stage and residual stress stage. The addition of fibers into concrete remarkably improves the ductility of concrete due to the fiber bridging effect. Moreover, the negative curing temperatures drastically inhibit the hydration reaction of concrete. Denser microstructure, more hydration products and good fiber–matrix binding quality can be observed in the concrete samples cured at the higher temperatures.